2013
DOI: 10.1007/s10396-013-0495-7
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and surgical approach for a schwannoma of the hand

Abstract: Schwannomas are benign encapsulated neoplasms of the peripheral nerve sheath. Clinical diagnosis is often difficult, and final diagnosis is usually based on histopathological findings. Imaging techniques, such as magnetic resonance imaging and ultrasonography, can be optimized to improve assessment prior to surgical treatment. The present case demonstrates that high-resolution sonography can be useful in assessing the underlying cause of median nerve pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the T2-weighted image, schwannoma appears bright with a heterogeneous hyperintensity. A lower intensity signal at the core of the mass (bull's eye or target sign) may also be observed in schwannoma and in another peripheral nerve sheath tumor, neurofibroma [2] , [7] , [10] . In our case, the MRI findings strongly supported a peripheral nerve sheath tumor diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the T2-weighted image, schwannoma appears bright with a heterogeneous hyperintensity. A lower intensity signal at the core of the mass (bull's eye or target sign) may also be observed in schwannoma and in another peripheral nerve sheath tumor, neurofibroma [2] , [7] , [10] . In our case, the MRI findings strongly supported a peripheral nerve sheath tumor diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered the most common form of peripheral nerve sheath tumor. However, its occurrence is rare (only accounts for less than 5 % of all soft tissue tumors) and mostly encountered during the third and sixth decades of life [1] , [2] . Clinical identification and treatment of schwannomas is challenging since these tumors can manifest as a painless growth for years before they are discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Simon et al demonstrated that high-resolution ultrasonography (HRUS) correctly differentiated tumor and motor fascicles when compared with intraoperative electrophysiologic monitoring. 9 Differentiating between PNS and VM with HRUS is difficult as blood can often be stagnant in slow-flow VMs. However, Zardi et al demonstrate the benefit of power flow sonography in identifying "red" and "blue" vascular signal spots that indicate vascularity which is present in PNSs but absent in VMs.…”
mentioning
confidence: 99%
“…However, Zardi et al demonstrate the benefit of power flow sonography in identifying "red" and "blue" vascular signal spots that indicate vascularity which is present in PNSs but absent in VMs. 9 Likewise, VMs will demonstrate compressibility given even light pressure from a US scanner head, whereas PNS are not compressible with scanner head pressure. MRI with tractography demonstrated good correspondence with both HRUS and intraoperative electrophysiologic monitoring.…”
mentioning
confidence: 99%